Remaining useful lifetime prediction of gas turbine bearings based on experiment vibration signals data - Saadat, Boulanouar; Hafaifa, Ahmed; Bennani, Ali; Hadroug, Nadji; Kouzou, Abdellah; Haddar, Mohamed (Journal of Vibration Testing and System Dynamics, 2026)
Gas turbines are widely found in industries, especially in gas compressor stations, where they are used to ensure the transportation of gas in high pressure pipelines over a long distance. Nevertheless, these rotating machines are subject to vibrations due to the influence of several causes, such as mass imbalance and shaft misalignment. These vibrations can affect directly the bearings, where their lifespan can be shorten remarkably. Furthermore they can be damaged causing catastrophic failure in the gas turbine and its installation. The main purpose of this paper is to develop an approach that can provide the estimated remaining life of the gas turbine bearings based on the vibration signals obtained via installed sensors. This approach allows us to estimate the optimal expected life of the studied gas turbine bearings by the prediction of the expected failures times. The obtained result under the proposed approach is satisfactory and shows that the use of the proposed approach can avoid the costly damage caused by the mentioned failures in the gas turbine under the imposed constraints.